Acute renal failure with ACE inhibition in aortic coarctation. Issue 830 (December 1994) - Woodmansey, P. A.; Yeo, W. W.; Jackson, P. R.; Ramsay, L. E.
Abstract : A 43 year old man with inoperable aortic coarctation and severe hypertension requiring near maximal anti-hypertensive treatment was admitted in severe heart failure. After 2 weeks of treatment the heart failure and blood pressure were incompletely controlled and angiotensin converting enzyme (ACE) inhibitor was started. Serum creatinine was normal before starting the ACE inhibitor and on discharge from hospital. The patient was re-admitted a week later with gross fluid retention and in renal failure. In the absence of alternative causes, a diagnosis of ACE inhibitor-induced renal failure was made and treatment was stopped. The patient required haemodialysis for 2 days and within 1 week the renal function had reverted to normal and has remained so for 1 year. We propose that the renal haemodynamics in severe aortic coarctation are similar to those in bilateral severe renal artery stenosis and advise caution in the use of ACE inhibitors for adults with aortic coarctation.